THE SIGNIFICANCE OF TRADITIONAL DAYAK CULINARY HERITAGE IN ESTABLISHING DESTINATION BRAND IDENTITY FOR TOURISM DEVELOPMENT IN CENTRAL KALIMANTAN - Mau, Daniel Pandu; Mahmudi, Mahmudi; Mau, Yesarela Pandu; Artana, I Wayan Arta (JURNAL KEPARIWISATAAN, 2024)
This study aimed to examine the growth of the traditional culinary industry sector in Central Kalimantan and its relationship with tourist destinations, emphasizing its role as a branding tool that shapes the destination brand identity in Central Kalimantan. The research methodology employed was qualitative with a focused case study approach in Central Kalimantan. Data were obtained through triangulation techniques, including observation, interviews, and the analysis of documentary data, involving various informants such as officials from the Ministry of Culture and Tourism, academicians, tourism destination managers, culinary entrepreneurs, tourists, and local communities. Data analysis utilized an interactive model comprising data collection, data condensation, data display, and conclusion stages. The research findings highlighted the diversity of Dayak culinary offerings in Central Kalimantan, including Juhu Umbut Rotan, Juhu Singkah Enyuh, Juhu Kujang, Chips made of Kalakai, Kalumpe, Sambal Kandas Sarai, and Kenta through the Mangenta process, demonstrating positive impacts on the development of tourist destinations. Furthermore, Dayak culinary practices were elevated as a branding element capable of shaping destination identity. The synergy between the government and local communities is vital in promoting Dayak culinary heritage to fortify destination brand identity and boost tourism allure. Through cohesive collaboration, Central Kalimantan can effectively leverage Dayak cuisine's distinctiveness to build a robust and sustainable destination brand. To maximize this potential, fostering strong synergy among the government, local communities, and culinary entrepreneurs is crucial. Proactive government engagement, sustained support for culinary entrepreneurs, organizing culinary festivals to enhance global awareness, targeted backing for enterprises like MEFs Food & Snacks, active community participation in digital marketing, and continuous research to monitor market trends are pivotal.